Critical environmental education in tertiary English language teaching (ELT): A collaborative digital storytelling project - Putri, I Gusti Agung Paramitha Eka (Universitas Pendidikan Indonesia, 2018)
Environmental issues have recently been incorporated into English materials. Hundreds of ELT materials concerning environmental issues are available worldwide in mainstream or assigned coursebooks and may simply be adapted by teachers for their classroom use. To respond to this, the present study explores an initial endeavor to integrate critical environmental education into ELT in a higher education context. In this study, a collaborative digital storytelling project was enacted. Student teachers created digital stories about Subak, their local environment, to evaluate its problems and propose solutions to the problems. Data gleaned from a questionnaire, an interview, and digital stories were thematically analyzed. Findings indicate that digital storytelling served as a multidimensional platform for student teachers to explore economic, political, and social aspects linked to subak. Thus, their digital stories could be considered as authentic materials for environmental education. This suggests that digital storytelling (DST) is a form of a powerful campaign against environmental destruction. The main contributions of this article are to provide empirical evidence regarding the implementation of a collaborative DST project in higher education and to show pedagogical implications for English language teaching (ELT) and critical environmental pedagogy.